Chapter 14. Central bank digital currencies, Internet of Things, and blockchain: prospects and challenges for Islamic finance - Al-Ansari, Khalid Ahmed (Islamic finance in the digital age, 2024)
This chapter explains Central Bank Digital Currencies (CBDCs) types, design format, advantages, impact, privacy considerations, and examples of launched CBDCs. Furthermore, it illustrates Internet of Things (IoT) technology implementation in financial institutions and addresses the security weakness of combining IoT with blockchain (BIoT) which can eliminate this deficiency. The study concludes with recommendations, including evaluating and using a stablecoin for payment and integrating Distributed Ledger Technology (DLT) and BIoT in daily operations to boost productivity and enhance security within Islamic finance institutions.